Words in the bilingual brain: an fNIRS brain imaging investigation of lexical processing in sign-speech bimodal bilinguals - Kovelman, Ioulia; Shalinsky, Mark H.; Berens, Melody S.; Petitto, Laura-Ann (Frontiers in Human Neuroscience, 2014)
Early bilingual exposure, especially exposure to two languages in different modalities such as speech and sign, can profoundly affect an individual’s language, culture and cognition. Here we explore the hypothesis that bimodal dual language exposure can also affect the brain’s organization for language. These changes occur across brain regions universally important for language and parietal regions especially critical for sign language (Newman et al., Nature Neuroscience, 2002). We investigated three groups of participants (N=29) that completed a word repetition task in American Sign Language (ASL) during fNIRS brain imaging. Those groups were (i) hearing ASL-English bimodal bilinguals (n=5), (ii) deaf American Sign Language (ASL) signers (n=7), and (iii) English monolinguals naïve to sign language (n=17). The key finding of the present study is that bimodal bilinguals showed reduced activation in left parietal regions relative to deaf ASL signers when asked to use only ASL. In contrast, this group of bimodal signers showed greater activation in left temporo-parietal regions relative to English monolinguals when asked to switch between their two languages (Kovelman, Petitto et al., 2009). Converging evidence now suggest that bimodal bilingual experience changes the brain bases of language, including the left temporo-parietal regions known to be critical for sign language processing (Emmorey et al., 2007). The results provide insight into the resilience and constraints of neural plasticity for language and bilingualism.